Legal Regulations and Developments of Cryptocurrencies in India and Russia: A Comparative Analysis - Gupta, Gazal; Yadav, Amit; Gupta, Aditya (Law, State and Telecommunications Review, 2024)
[Purpose] This article addresses the lack of legislation in India to govern digital currencies, as well as the legality of Bitcoin in comparison to Russia's ban on other digital assets for payment regulation, highlighting the necessity for effective legislation once all around the world. It further delves into potential misuse of private cryptocurrencies in a variety of ways while placing upon the need for both countries to form a new digital currency regulatory authority. [Methodology/Approach/Design] This paper probes into the existing legal regulations for Cryptocurrency in India, Russia and other countries by using primary and secondary data throughout the paper. The primary data have been taken from legitimate government sources such as Russia's federal law and other bills and laws enacted in India, such as the "Banning of Cryptocurrency and Regulation of Official Digital Currency Bill, 2019" and "The Cryptocurrency and Regulation of Official Digital Currency Bill, 2021." Various judgments like the case of Internet and Mobile Association of India v. Reserve Bank of India and Dwaipayan Bhowmick v. Union Of India and Ors. have been taken out from Manupatra which is an online database for legal research. Government reports and notifications from the Indian, Russian and US government have also been examined. The secondary data include numerous news articles from Times of India, The Mirror, India Times, The Moscow Times, Telegraph, The UK News and other new sites. Lastly, articles by various researchers like Bohme et al, Dyhrberg and Kim have also been thoroughly analysed. [Findings] It was concluded that legalising Cryptocurrency through codified laws, appropriate approval for digital currencies through regulatory authorities, establishing clear definition of ‘cryptocurrency’, uniform taxation for all types of Cryptocurrencies, updation of penal laws and setting imprisonment for cryptocurrency regulation violation seem to be some effective solutions to reignite the Indian and Russian Economies. [Practical Implications] The practical implication lies in the fact that the use of cryptocurrencies is increasing on a daily basis, but neither the national government nor the world organizations has made any steps to control the market for virtual currencies.